MAX phases and ultra-high temperature ceramics for extreme environments - Low, It Meng; Sakka, Y.; Hu, C. (2013)
Ceramics are a versatile material, more so than is widely known. They are thermal resistant, poor electrical conductors, insulators against nuclear radiation, and not easily damaged, making ceramics a key component in many industrial processes. MAX Phases and Ultra-High Temperature Ceramics for Extreme Environments investigates a new class of ultra-durable ceramic materials, which exhibit characteristics of both ceramics and metals. Readers will explore recent advances in the manufacturing of ceramic materials that improve their durability and other physical properties, enhancing their overall usability and cost-effectiveness. This book will be of primary use to researchers, academics, and practitioners in chemical, mechanical, and electrical engineering. This book is part of the Research Essentials collection.